INDICATORS FOR DIGITALIZATION OF SUSTAINABLE DEVELOPMENT GOALS IN PEEX PROGRAM - Sergey N. Bobylev; Olga Yu. Chereshnya; Markku Kulmala; Hanna K. Lappalainen; Tuukka Petäjä; Svetlana V. Solov’eva; Vladimir S. Tikunov; Veli-Pekka Tynkkynen (Geography, Environment, Sustainability)
This article describes the Pan-Eurasian Experiment (PEEX) program and indicators for monitoring of implementation and digitalization of Sustainable Development Goals (SDG) inRussia, especially environmental goals. The authors considered the possibility of integration and identification of the methodological approaches of the socio-economic research to environmental sciences. Paper gives insights into the international framework of the United nations, addreses several relevant indicators to be monitored in a Russian perspective and summarizes shortly the status of the monitoring activities and provide an overview on the main tasks for the upcoming years to reach the sustainable development goals established by the United Nations. The tasks to which the Goals divided are considered in detail. The indicators of Russian statistics that can be used to monitor the implementation of these tasks are determined. It is shown, that more detailed regional analysis and new data is needed in order to quantify the feedbackloops.